Density and Biomass of Brachyurans from Intertidal Regions in and around Mumbai Coast, India - Mayura Khot; Bhaskar Shenoy; A.K. Jaiswar (Journal of Indian Fisheries Association, 2019)
The crabs are not only finger licking delicacy in coastal cuisines but plays pivotal role on aquatic trophic structure. Hence, the information on their abundance and biomass is essential for management of fishery resources. The present study was conducted to study the density and biomass of crabs from intertidal regions in and around Mumbai coast, India. A total of 48 species of crabs belonging to 21 families were recorded. Overall, maximum contribution, in terms of density and biomass, was made by members of family Portunidae (19%) followed by Xanthidae (11%) and Pilumnidae (7%).The avergae density of crabs ranged from 2 to 5 individuals/m2 and 28.6 to 180 g/m2. The Spearman rank correlations revealed significant correlation (p=0.01, P<0.05) between salinity and density whereas other environmental variables showed no such significant correlation. A one-way ANOVA revealed non-significant temporal (p=0.18, P>0.05) and spatial (p=0.39, P> 0.05) variations in crab abundances. Maximum density was recorded for C. lucifera, C. annulata, Menippe rumhii, Thalamita crenata, Dotilla blandfordi and Xenophthalmus wolfii, whereas, maximum biomass was recorded for C. lucifera, C. annulata, Menippe rumhii, Ashtoret lunaris, Leptodius exaratus, Grapsus albolineatus, Myomenniepe hardwickki and Thalamita crenata. Girgaon and Uttan areas were found to be more polluted when compared to Marine drive and Bandstand. However, a long term monitoring is recommended to ascertain the eﬀect of human exploitation on density and biomass.